Prediction of engine oil degradation due to temperature effect by using optical spectroscopy: article / Nor Syuhadah Endut ... [et al.] - Endut, Nor Syuhadah; Md. Idros, Mohd Faizul; Osman, Fairul Nazmie; Mohd. Noor, Uzer (2009)
This paper presents the prediction ofthe engine oil degradation by using non distractive testing. The main objective of this project is to predict the worst condition of engine oil need to change based on its colour for maximum used. Two types of engine oil were used as samples in this project from grade SAE 10W40 and 20W50. A method have been used is heating the engine oil with inductance coil for 5 minute and then cool it about half an hour before continue heating for other 5 minute. This process repeat continuously until 100 minute and samples takes at every l0 minute after cooling process. The temperature of the engine oil is about l30oc. A spectrometer is used to measure the percentage reflectance of the samples. Data was arranged in the Microsoft excel and analyzed in order to predict the degradation ofthe engine oil.